2022
DOI: 10.1093/arclin/acac004
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Profiles in Patients With Persisting Cognitive Symptoms Associated With COVID-19

Abstract: Objective A subset of individuals with coronavirus disease 2019 (COVID-19) appears to develop persisting cognitive and medical symptoms. Research in the acute stages of illness, generally utilizing cognitive screening measures or case reports, suggests presence of deficits in attention and executive function. This observational study investigated cognitive functioning among individuals with persistent cognitive complaints about 5.5 months after COVID-19 infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
48
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 31 publications
12
48
1
1
Order By: Relevance
“…Taken altogether, these findings suggest a relationship between fatigue, neuropsychiatric and cognitive disorders. However, with the notable exception of Krishnan et al [ 24 ], few studies have investigated whether these three dimensions of the post-COVID-19 condition are interrelated or are independent entities. In the present study, we explored how associated these symptomologies are in a larger sample of patients who were diagnosed with COVID-19 and presented with subjective cognitive complaints on average 8 months after disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…Taken altogether, these findings suggest a relationship between fatigue, neuropsychiatric and cognitive disorders. However, with the notable exception of Krishnan et al [ 24 ], few studies have investigated whether these three dimensions of the post-COVID-19 condition are interrelated or are independent entities. In the present study, we explored how associated these symptomologies are in a larger sample of patients who were diagnosed with COVID-19 and presented with subjective cognitive complaints on average 8 months after disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive and olfactory symptoms are often reported among the most frequent symptoms after acute infection [ 31 ]. The main cognitive domains involved in post-COVID syndrome are attention/executive functioning and episodic memory [ 28 , 32 ]. In this study, we included a comprehensive protocol for neuropsychological assessment including the main cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairments in areas of working memory, executive functioning, memory, visuospatial ability, abstraction, and orientation have also been found [ 17 , 27 ]. Recovery in some or most of these areas in the post-acute phase of the illness has been demonstrated [ 28 ]; however, there are persisting deficits seen in this phase, including patients who were not hospitalized [ 29 ].…”
Section: Neurocognitive and Functional Outcomementioning
confidence: 99%
“…Cognitive deficits were widespread in those with and without ICU stays and occurred most commonly on measures of oral processing speed and verbal fluency as well as learning and memory [ 30 , 31 ]. Those who required hospitalization were also more likely to have objective cognitive deficits persisting after the acute phase [ 29 ]. However, there have also been conflicting findings suggested that cognitive deficits are not greater in those requiring higher levels of acute care [ 35 , 36 ].…”
Section: Neurocognitive and Functional Outcomementioning
confidence: 99%